Application of naturopathy management on non-alcoholic fatty liver and cholilithiasis – A case report - Princy, Anto; Poornachandran, Prabu; Narayanasamy, Mangaiarkarasi (Indian Journal of Integrative Medicine, 2022)
Cholelithiasis and Non-alcoholic Fatty liver disease are the most common hepatobiliary disorder which are reported in hospitals. Damage to the hepatic cells due to high cholesterol, improper food and imbalanced bile results in the cascade of hepatobiliary disorders. Here is a case of a 64-year male patient with a previous history of cholilithiasis has indigestion and frequent burping for the past 2 months. In the ultra-sonogram findings, he was diagnosed with Cholelithiasis, Fatty liver grade 1 with simple hepatic cyst (1.3 cm), hypercholesterolemia. This case study was done to investigate the effect of Dietary management and liver flush in Cholelithiasis and fatty liver. The patient was given 10 days fruit diet and given liver flush on the 11thday followed by dietary modification for a month. After the treatment his cholesterol level reduced from 207 to 149 while bilirubin level also showed reduction from 2.44 to 2.17. Ultra-sonogram findings shows that normal liver size and echo texture and absence of calculi in Gall bladder. Under this case study we can conclude that there is a positive improvement in the hepatobiliary disorder by following the Naturopathic management